PENERAPAN PRINSIP AKUNTABILITAS PADA PEMBIAYAAN KEGIATAN EKSTRAKURIKULER KEAGAMAAN DI MADRASAH ALIYAH PARADIGMA PALEMBANG - Nazarudin Nazarudin; Kris Setyaningsih; Masayu Nadya Ardelya Kesumah (Adaara: Jurnal Manajemen Pendidikan Islam, 2020)
The purpose of this study is to analyze the application of the principle of accountability in the financing of religious extracurricular activities in the Madrasah Aliyah Paradigma Palembang and the factors that support and inhibit the application of the principle of accountability in the financing of religious extracurricular activities in the Madrasah Aliyah Paradigma Palembang. This type of research is field research with a descriptive qualitative approach. The informants of this research are the madrasa head, Madrasa deputy head, madrasa treasurer and religious extracurricular adviser. The data collection tools used were interviews, observation and documentation study. After the data is collected then it is analyzed using the Milies and Huberman approach. Activities in data analysis in this approach are: data reduction, data display, and conclusion drawing / verification. Based on the results of research and discussion, conclusions can be drawn, namely: Application of the Principle of Accountability in Financing Religious Extracurricular Activities in Madrasah Aliyah Paradigma Palembang has been going well. It is clear that transparency of education providers is open to receiving input and including various components in budget management. Meet clear performance standards in every activity that can serve as benchmarks in carrying out duties, functions and authority with a full sense of responsibility. Participation from all parties to create a conducive atmosphere for each other. Factors supporting the application of the principle of accountability are setting clear goals and objectives. Solid institutional structure. Establish a clear and directed policy. Planning that is realistic, detailed and in accordance with needs. The inhibiting factors are the limitations of research in obtaining other supporting data sources regarding the financing of extracurricular activities such as evidence of financial allocation / expenditure transactions and accountability reports.